2011
DOI: 10.1002/ajh.22170
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of immune thrombocytopenia in elderly: Results from a single center case‐controlled study

Abstract: The management of ITP in elderly raises several questions that have not been fully addressed in the literature. To assess the impact of ITP in elderly, a case-control study was performed. The main characteristics at onset and the outcome of ITP in 55 patients aged of 70 years and above (cases) were compared with those of 97 younger adults (controls) seen at the same tertiary referral institution. The mean age at diagnosis was respectively 77.8 ± 6.1 years (cases) and 40.3 ± 14.9 years (controls). While the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 20 publications
10
43
0
Order By: Relevance
“…The analytical model developed in this study estimated that patients older than 60 years with a platelet count <30 9 10 9 / l had a predicted 5-year bleeding risk of 48% as compared with 2Á2% for ITP patients younger than 40 years. In a casecontrol study, our group confirmed that at equivalent platelet count, bleeding manifestations were both more frequent and more severe in older patients (>70 years) than younger patients (Michel et al, 2011). In the largest study of older adults with ITP including more than 500 patients, both age and platelet count were risk factors for severe bleeding (Zhou et al, 2013).…”
Section: How Is Itp Diagnosed In the Elderly?supporting
confidence: 52%
See 2 more Smart Citations
“…The analytical model developed in this study estimated that patients older than 60 years with a platelet count <30 9 10 9 / l had a predicted 5-year bleeding risk of 48% as compared with 2Á2% for ITP patients younger than 40 years. In a casecontrol study, our group confirmed that at equivalent platelet count, bleeding manifestations were both more frequent and more severe in older patients (>70 years) than younger patients (Michel et al, 2011). In the largest study of older adults with ITP including more than 500 patients, both age and platelet count were risk factors for severe bleeding (Zhou et al, 2013).…”
Section: How Is Itp Diagnosed In the Elderly?supporting
confidence: 52%
“…Thus, most guidelines for adult ITP suggest that treatment should be considered when the platelet count is <30 9 10 9 /l and/or with bleeding manifestations (British Committee for Standards in Haematology General Haematology Task Force 2003; Cines & Bussel, 2005;Rodeghiero et al, 2009;Provan et al, 2010;Neunert et al, 2011). In line with these recommendations, a recent retrospective analysis of a population of older ITP patients confirmed that severe bleeding mostly occurred in patients with a platelet count <20 9 10 9 /l (Michel et al, 2011). However, two limits must be underlined: (i) most patients included in these studies were younger than 75 years and (ii) some with a platelet count >50 9 10 9 /l died due to intracranial haemorrhage.…”
Section: Nomentioning
confidence: 97%
See 1 more Smart Citation
“…The role of exposure to anticoagulant or antiaggregant in these events needs further investigation. 14 The limitations of this study are inherent to all studies in administrative databases. We cannot rule out some misclassifications.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, and solely to indicate this fact, this article is hereby marked "advertisement" in accordance with 18 USC section 1734. patients (n 5 340) were included. 13 Bleeding risk might increase with age, 14 but faithful assessment of such rare events needs larger cohorts.…”
Section: Introductionmentioning
confidence: 99%